2013
DOI: 10.4038/cmj.v58i2.5681
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lankan fetal/ birthweight charts: validation of global reference for fetal weight and birthweight percentiles

Abstract: The findings of the study show that the observed distribution of birthweight fitted well with the reference range derived from the WHO global reference range adapted to Sri Lankan population. WHO reference charts can be used effectively in Sri Lankan population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Gestational age specific birth weights with fitted 10 th , 50 th and 90 th centiles compared with gestation specific birth weights centiles obtained by applying the mean birth weight at 40 weeks gestation and its coefficient of variation (standard deviation expressed as a percentage of the mean birth weight) in the study sample to the weight percentiles calculator of the global reference for fetal weight and birth weight percentiles [16] (n=1602). Table 3, The gestation specific birth weight centiles obtained from the study compared with the calculated centiles obtained by applying the mean birth weight and its coefficient of variation of those who delivered at 40 weeks gestation to the weight percentiles calculator of the global reference for fetal weight and birth weight percentiles [16] Original article between 280-286 days gestation, while in the current study there were 464 out of the 1602 births occurring between 280-286 days gestation [19]. Furthermore, in the global reference for fetal weight and birth weight percentiles, "an average gestational age of 40.5 weeks" has been used for the calculations, while in the current study the median gestational age at delivery was 275 days gestation [16].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Gestational age specific birth weights with fitted 10 th , 50 th and 90 th centiles compared with gestation specific birth weights centiles obtained by applying the mean birth weight at 40 weeks gestation and its coefficient of variation (standard deviation expressed as a percentage of the mean birth weight) in the study sample to the weight percentiles calculator of the global reference for fetal weight and birth weight percentiles [16] (n=1602). Table 3, The gestation specific birth weight centiles obtained from the study compared with the calculated centiles obtained by applying the mean birth weight and its coefficient of variation of those who delivered at 40 weeks gestation to the weight percentiles calculator of the global reference for fetal weight and birth weight percentiles [16] Original article between 280-286 days gestation, while in the current study there were 464 out of the 1602 births occurring between 280-286 days gestation [19]. Furthermore, in the global reference for fetal weight and birth weight percentiles, "an average gestational age of 40.5 weeks" has been used for the calculations, while in the current study the median gestational age at delivery was 275 days gestation [16].…”
Section: Discussionmentioning
confidence: 86%
“…However, this could also be due to a true difference, and this should be explored further by a larger, multicenter, national study. The number of preterm deliveries and their observed birth weights, were not reported in the sample of 411 used for the study which validated the global reference for fetal weight and birth weight percentiles for use in Sri Lanka [19].…”
Section: Discussionmentioning
confidence: 95%
“…5 kg, polyhy-dramnios, blood pressure >160/110mmHg, placenta praevia, abruptio placentae, pre-labor rupture of mem-branes and failed induction of labor. In Sri Lanka, the mean birth weight of a neonate at 40 weeks of gestation and the 90 th centile are estimated to be approximately 3 kg and 3.5 kg respectively [18]. Audits carried out in the unit have indicated that neonatal birth weight of >3.5 kg and induction of labor have increased risks of postpartum haemorrhage (PPH).…”
Section: Methodsmentioning
confidence: 99%
“…The mean birthweight of local population is similar, and the adapted reference range would identify most SGA fetuses including severe SGA fetuses correctly. It would also identify almost all the large for gestational age babies with a birthweight >90th centile 19 . Hence, WHO reference charts can be used effectively in Sri Lankan population 19 .…”
Section: Validation Of Sri Lankan Birthweight Referencementioning
confidence: 99%
“…It would also identify almost all the large for gestational age babies with a birthweight >90th centile 19 . Hence, WHO reference charts can be used effectively in Sri Lankan population 19 .…”
Section: Validation Of Sri Lankan Birthweight Referencementioning
confidence: 99%